Pengaruh Human Relation, Disiplin Kerja dan Motivasi terhadap Kepuasan Kerja Karyawan pada PT. BPR Sadhu Artha (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
To create job satisfaction, companies can start by creating harmonious work relationships, disciplined and highly motivated employees. The problem and the objectives of this study: how and to find out the influence of human relations, work discipline and motivation on job satisfaction. The sample used was 32 respondents, the research method used was quantitative. The data analysis techniques used are validity test, reability, classical assumption, multiple linear regression, coefficient of determination, multiple correlation analysis, t test and F test. This study showed that Partially, human relations, work discipline, and motivation have a significant positive effect on job satisfaction. Simultaneously, these three variables have a significant effect on job satisfaction, the magnitude of which is 58.1%. The advice that researchers can give is PT. BPR Sadhu Artha in Sukawati is expected to foster better relations between employees, routinely make outing activities, always conduct periodic evaluations of employee work results, and always supervise employees at work, so employees are able to work carefully and independently. The leader of PT. BPR Sadhu Artha in Sukawati is expected to increase the intensity of providing motivation to employees.